2011
DOI: 10.1038/jid.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

Fli1 Is a Negative Regulator of Estrogen Receptor α in Dermal Fibroblasts

Abstract: Estrogen is an important regulator of dermal fibroblast functions, including extracellular matrix (ECM) synthesis. Estrogen mediates its effects through estrogen receptors (ERs), ERα and ERβ; however, regulation of ERs in dermal fibroblasts remains poorly understood. Friend leukemia integration factor 1 (Fli1), a member of the Ets transcription factor family, has been shown to play a pivotal role in regulation of the ECM genes in dermal fibroblasts. The aim of this study was to examine a possible interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…Furthermore ER protein was undetectable in western blotting experiments. This is in apparent contrast with previous reports that documented the expression of ERs in human skin [ 17 , 38 40 ]. ERβ was the main ER expressed in fibroblasts whereas ER was expressed in sebocytes rather than fibroblasts [ 13 ].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Furthermore ER protein was undetectable in western blotting experiments. This is in apparent contrast with previous reports that documented the expression of ERs in human skin [ 17 , 38 40 ]. ERβ was the main ER expressed in fibroblasts whereas ER was expressed in sebocytes rather than fibroblasts [ 13 ].…”
Section: Discussioncontrasting
confidence: 98%
“…However, besides changes in skin extracellular matrix content, the function of resident cells in the skin are likely influenced by estrogen. Although the role of exogenous estrogens in the integrity of human dermal fibroblasts has not been investigated, changes in fibroblast phenotype have been noted in aging skin [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of these ER isoforms is either undetectable or nominal in the HFFs used for the screen, suggesting that the drug functions in an ER-independent manner ( 31 , 32 ). We tested this by assessing the growth of β-Gal-expressing parasites in tamoxifen-treated MCF7 cells, which express the ER ( 32 ), and in HeLa cells and murine embryonic fibroblasts (MEFs) that, like HFFs, are ER deficient or express the ER at significantly lower levels than MCF7 cells do ( 33 , 34 ). We found that parasite growth in all three cell types was similarly affected by tamoxifen, although the IC 50 in MCF7 cells was slightly lower ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression levels were determined by quantitative real-time PCR, as described previously (Hattori et al, 2011). mRNA levels were normalized to those of the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene.…”
Section: Methodsmentioning
confidence: 99%
“…Human dermal fibroblasts were lysed and subjected to immunoblotting, as described previously (Hattori et al, 2011). Primary antibodies used (1:1000): phospho-PDGFRα, PDGFRα, phospho-PDGFRβ, PDGFRβ, phospho-ERK1/2, ERK1/2, phospho-Akt, Akt from Cell Signaling (Danvers, MA), Type I collagen from Southern Biotech (Birmingham, AL), CCN2 from Santa Cruz Biotechnology (Dallas, TX), periostin from Abcam (Cambridge, MA) and β-actin from Sigma (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%